Sikap Penghindaran Pajak, Strategi Pendanaan dan Manajemen Laba Perusahaan - Ferry Irawan; Febriansyah Utama Putra (Owner : Riset dan Jurnal Akuntansi, 2022)
Companies need to manage their financial performance well. Companies tneed also to establishe their funding strategies for daily activities. This quantitative research aims to investigate the relationship among tax avoidance, funding strategy and earnings management. We use 56-listed companies from 2013 to 2016. The samples are obtained throughout purposive sampling method. There are several important findings. First, tax avoidance action decrease the amount of profits. Second, the increase in retained earnings will not promote the earnings management. Third, The increasing of equity-funding will cause managers to improve the amount of profits. Fourth, both Short-term liabilites and long-term liabilities will increase the earnings management.